Diseases of the Abdomen and Pelvis 2018-2021: Diagnostic Imaging - IDKD Book - Hodler, Juerg; Kubik-Huch, Rahel A.; von Schulthess, Gustav K. (IDKD Springer Series, 2018)
Gastrointestinal disease; PET/CT; Radiology; X-ray; IDKD; Davos